Dr. Angel Franco Medina — Deep Plane Facelift — San Luis Potosí - Medina, Angel Franco (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Angel Franco Medina, practicing in San Luis Potosí, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003187; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; san luis potosí